Synthesis, Characterization and Antibacterial Activity of Some Halo Substituted Schiff Bases - S. B. Junne; Archana B. Kadam; S. L. Shinde; G. S. Waghamare; Y. B. Vibhute (E-Journal of Chemistry)
Some new halo substituted Schiff bases have been prepared from different aromatic aldehydes and a series of substituted aromatic amines to form a number of potentially biologically active compounds. The structures of the Schiff bases have been characterized by using IR and 1HNMR spectroscopy. These compounds were screened against human pathogenic bacteria by agar diffusion method. Ampicillin was used as control.